Soluble, Colloidal, and Particulate Iron Across the Hydrothermal Vent Mixing Zones in Broken Spur and Rainbow, Mid-Atlantic Ridge - Yücel, Mustafa; Sevgen, Serhat; Le Bris, Nadine (Frontiers in Microbiology, 2021)
The slow-spreading Mid-Atlantic Ridge (MAR) forms geological heterogeneity throughout the ridge system by deep crustal faults and their resultant tectonic valleys, which results in the existence of different types of hydrothermal vent fields. Therefore, investigating MAR hydrothermal systems opens a gate to understanding the concentration ranges of ecosystem-limiting metals emanating from compositionally distinct fluids for both near-field chemosynthetic ecosystems and far-field transport into the ocean interiors. Here we present novel data regarding on-board measured, size fractionated soluble, colloidal and particulate iron concentrations from the 2018 R/V L’Atalante – ROV Victor research expedition, during which samples were taken from the mixing zone of black smokers using a ROV-assisted plume sampling. Iron size fractionation (<20, 20-200 and >200 nm) data were obtained from on-board sequential filtering, followed by measurement via ferrozine assay and spectrophotometric detection at 562 nm. Our results showed the persistent presence of a nanoparticulate/colloidal phase (retained within 20-200 nm filtrates) even in high-temperature samples. A significant fraction of this phase was retrievable only under treatment with HNO3 – a strong acid known to attack and dissolve pyrite nanocrystals. Upon mixing with colder bottom waters and removal of iron in the higher parts of the buoyant plume, the larger size fractions became dominant as the total iron levels decreased but it was still possible to detect significant (micromolar) levels of nanoparticulate Fe even in samples collected 5 m above the orifice in the rising plume. The coolest sample (<10 C) still contained more than 1 µM of only nitric-acid leachable nanoparticle/colloidal, at least 200 times higher than a typical Fe concentration in the non-buoyant plume. Our results support previous reports of dissolved Fe in MAR vent plumes and we propose that this recalcitrant Fe pool – surviving immediate precipitation – contributes to maintaining high hydrothermal iron fluxes to the deep ocean.